2024
DOI: 10.1002/ejoc.202301114
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Supported Heterogeneous Dirhodium(II) Catalyst for Nitrene and Carbene Transfer Reactions

Vanaparthi Satheesh,
Indunil Alahakoon,
Kendra K. Shrestha
et al.

Abstract: The bimetallic rhodium(II) paddlewheel (Rh2A4) complex is one of the most reactive classes of rhodium catalysts, well‐renowned for the most demanding carbene‐ and nitrene‐transfer reactions. In view of its importance in modern synthetic chemistry, we herein report a facile approach for preparing a self‐supported and reusable dirhodium(II) polymer‐based heterogeneous catalyst through a reductive ligation protocol. The catalyst displays good reactivity for inter‐ and intramolecular nitrene‐ and carbene‐insertion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…N 2 adsorption−desorption isotherms indicated that both materials show low surface area of around 17 cm 2 /g, which may be ascribed to the interpenetration or stacking of coordination polymers during the synthesis of such materials (Figure 3a). 50 The pore volumes of Rh 1 -MOCP-1 and Rh 2 -MOCP-2 are 0.32 cm 2 /g and 0.38 cm 2 /g, respectively. The resulting high pore volume is most probably attributed to the aggregation of spherical particles.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…N 2 adsorption−desorption isotherms indicated that both materials show low surface area of around 17 cm 2 /g, which may be ascribed to the interpenetration or stacking of coordination polymers during the synthesis of such materials (Figure 3a). 50 The pore volumes of Rh 1 -MOCP-1 and Rh 2 -MOCP-2 are 0.32 cm 2 /g and 0.38 cm 2 /g, respectively. The resulting high pore volume is most probably attributed to the aggregation of spherical particles.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…These results indicated that carbon atoms C 1 and C 2 were produced during the synthesis of Rh 2 -MOCPs via Suzuki reaction between bromine groups of Rh 2 ( S -Br-NTTL) 4 and 1,4-phenylenediboronic acid or 4,4′-biphenyldiboronic acid, respectively. N 2 adsorption–desorption isotherms indicated that both materials show low surface area of around 17 cm 2 /g, which may be ascribed to the interpenetration or stacking of coordination polymers during the synthesis of such materials (Figure a) . The pore volumes of Rh 1 -MOCP-1 and Rh 2 -MOCP-2 are 0.32 cm 2 /g and 0.38 cm 2 /g, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations